Developing an Intervention to Improve Occupational Participation for Justice-Involved People with a Personality Disorder: Defining and Describing Intervention Components - Connell, Catriona (International journal of offender therapy and comparative criminology, 2022)
Occupational participation is undertaking personally meaningful and socially valued activities and roles. It is an important outcome for health and justice interventions, as it is integral to health and desistance. We report the third of a four-stage research project to develop an intervention to improve occupational participation for justice-involved people with a personality disorder in the community. We completed a Delphi survey to produce expert consensus on intervention components and their content, ascertain participant ratings of 28 factors for their level of influence on occupational participation, and the modifiability of the factors with this population. Thirty multi-disciplinary participants completed three survey rounds. Most factors were rated very influential, but few were considered easily modifiable. Participants agreed 121 statements describing intervention components and content. Twenty-seven statements did not reach consensus. In targeting specific factors in intervention, practitioners must balance their degree of influence with potential modifiability. The results will inform intervention manualization and modeling.